2014
DOI: 10.1007/s13205-014-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

An approach to low-density polyethylene biodegradation by Bacillus amyloliquefaciens

Abstract: Low-density polyethylene (LDPE) is a major cause of persistent and long-term environmental pollution. In this paper, two bacterial isolates Bacillus amyloliquefaciens (BSM-1) and Bacillus amyloliquefaciens (BSM-2) were isolated from municipal solid soil and used for polymer degradation studies. The microbial degradation LDPE was analyzed by dry weight reduction of LDPE film, change in pH of culture media, CO2 estimation, scanning electron microscopy (SEM), and fourier transform infrared FTIR spectroscopy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 13 publications
7
105
0
1
Order By: Relevance
“…The strong absorption peaks at 719 and 1472 cm -1 became weaker after fungal treatment whereas peaks at 2919 and 2850 cm -1 became intensified in the treated sample than the control one. The change in the peak values of almost all functional groups confirming the configurational change on polymer surface (Das and Kumar 2015;Gilan et al 2004;Drímal et al 2007;Hadad et al 2005;Arboleda et al 2004). …”
Section: Ftirmentioning
confidence: 71%
See 1 more Smart Citation
“…The strong absorption peaks at 719 and 1472 cm -1 became weaker after fungal treatment whereas peaks at 2919 and 2850 cm -1 became intensified in the treated sample than the control one. The change in the peak values of almost all functional groups confirming the configurational change on polymer surface (Das and Kumar 2015;Gilan et al 2004;Drímal et al 2007;Hadad et al 2005;Arboleda et al 2004). …”
Section: Ftirmentioning
confidence: 71%
“…The reduction in pH not only affirms the consumption of the polyethylene film as their sole carbon source (Duddu and Guntuku 2015;Das and Kumar 2015;Arutchelvi et al 2008). Microorganisms secrete variety of intra and extracellular enzymes into the media which might The dry weight of LDPE films were measured at different time points during the course of incubation.…”
Section: Ph Change In Biodegradation Processmentioning
confidence: 85%
“…Similarly, Ambika et al (2015) identified a marine bacterial strain as Achromobacter denitrificans S1 for LDPE degradation that was determined by NMR, XRD, TGA and GCMS analysis. Das and Kumar (2015) investigated a sample of municipal solid soil for distribution of polymer degrading microorganisms and isolated Bacillus amyloliquefaciens BSM-1 and B. amyloliquefaciens BSM-2. Das and Kumar (2015) found enhanced biodegradation with strain B. amyloliquefaciens BSM-2 in comparison to B. amyloliquefaciens BSM-1.…”
Section: Polyethylenementioning
confidence: 99%
“…Das and Kumar (2015) investigated a sample of municipal solid soil for distribution of polymer degrading microorganisms and isolated Bacillus amyloliquefaciens BSM-1 and B. amyloliquefaciens BSM-2. Das and Kumar (2015) found enhanced biodegradation with strain B. amyloliquefaciens BSM-2 in comparison to B. amyloliquefaciens BSM-1. The rate and efficiency of polymer degradation were determined by pH alteration in media, CO 2 evolution, weight loss, SEM and FT-IR analysis.…”
Section: Polyethylenementioning
confidence: 99%
“…Spectra were processed and analyzed using the OMNIC software (Thermo Fisher Scientific, USA). To interpret the FTIR spectra of microorganisms, we used data obtained for pure cultures of Bacillus amyloliquefaciens [25], Stenotrophomonas maltophilia [26], or various species of genera Aspergillus [27,28], Cladosporium [29], Ulocladium [29], and Bacillus [30].…”
Section: Micro-ftir Spectroscopy and Data Analysismentioning
confidence: 99%